2003
DOI: 10.1093/hmg/ddg108
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function analysis reveals the molecular determinants of the impaired biological function of DAX-1 mutants in AHC patients

Abstract: Mutations in the DAX-1 (NR0B1) gene cause the X-linked form of adrenal hypoplasia congenita (AHC), which is constantly found associated with hypogonadotropic hypogonadism (HHG). DAX-1 encodes an atypical orphan member of the nuclear hormone receptor superfamily. DAX-1 acts at multiple levels to repress the expression of genes involved in steroid hormone metabolism through a potent transcriptional repression domain present in its C-terminus, which is similar to the nuclear receptors' ligand binding domain. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…Among corepressors, DAX-1 was shown to interact with N-CoR [63] and Alien [64], even if further studies have ruled out a role of N-CoR as a bona fide DAX-1 corepressor [65]. However, site-directed mutagenesis of conserved surface residues in DAX-1, which in other nuclear receptors are involved in corepressor interaction, does not impair DAX-1 transcriptional silencing properties (see Section 6) [66]. These data suggest that cofactors different from known nuclear receptor corepressors mediate DAX-1 transcriptional silencing activity.…”
Section: Advances In Biologymentioning
confidence: 99%
See 3 more Smart Citations
“…Among corepressors, DAX-1 was shown to interact with N-CoR [63] and Alien [64], even if further studies have ruled out a role of N-CoR as a bona fide DAX-1 corepressor [65]. However, site-directed mutagenesis of conserved surface residues in DAX-1, which in other nuclear receptors are involved in corepressor interaction, does not impair DAX-1 transcriptional silencing properties (see Section 6) [66]. These data suggest that cofactors different from known nuclear receptor corepressors mediate DAX-1 transcriptional silencing activity.…”
Section: Advances In Biologymentioning
confidence: 99%
“…Third, the Dax-1 mutant ΔV271, which corresponds to the human AHC mutant ΔV269, behaves similarly to the wild type. However, the localization of this mutant is shifted to the cytoplasm (see below Section 6) [65,66] and it is difficult to explain how it may regulate promoter expression in the nucleus. Further studies are then needed to assess the role of potential interactions between DAX-1 and RNA transcriptional cofactors in the regulation of gene expression.…”
Section: Advances In Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…One missense mutation (L466R), which is located in the activation function 2 (AF2) core of a highly conserved region in the C-terminus, was shown to be defective in nuclear localization in spite of having an intact N-terminus and to impair the repression activity of DAX-1 (31). It has been also observed that several mutants from patients with AHC cannot localize into the nucleus, and thus this would partly explain the loss of function (53,54).…”
Section: R Molecular Basis Of Adrenal Insufficiencymentioning
confidence: 99%